Healthcare Provider Limitation of Life-Sustaining Treatment without Patient or Surrogate Consent. Issue 3 (September 2017) - Courtwright, Andrew; Rubin, Emily
In June 2015, the major North American and European critical care societies released new joint guidelines that delineate a process-based approach to resolving intractable conflicts over the appropriateness of providing or continuing LST.2 This article frames the new guidelines within the history, ethical arguments, legal landscape, and empirical evidence regarding limitation of LST without surrogate consent in cases of intractable conflict.